Cyberbullying: Tantangan Bagi Pengguna Media Sosial Terhadap Kesehatan Mental di Indonesia - Elmalia Maulidina Tsani; Wilvie Kamila Augest; Ruri Afriyan Hidayat; Nazwa Aurellia Sahfrina (Pusat Riset dan Inovasi Nasional, 2024)
Of the many negative impacts that social media has on its users, cyberbullying is one of the challenges that humans need to face today, especially in Indonesia. This research uses a literature review method that begins with a systematic literature review using the PRISMA flowchart to determine which articles are in accordance with the criteria and research topics. The results showed that the use of social media can become cyberbullying if not wise in using it. Indonesia as the largest social media user also faces this cyberbullying challenge. The victims of cyberbullying also often get mental health problems that can risk suicide after cyberbullying is directed at them.